Analysis of Schoolbooks in Ukrainian Language for Secondary School in (1945-1960-s) - Svitlana Kutova (Pedagogical Discourse, 2013)
The schoolbooks in Ukrainian language for secondary school (1945-1960-s): A.O.Zagrods’kyi «Grammar part II for the 6-7 forms»; Grammar of Ukrainian Language. Part II. Syntax. Schoolbook for the 6-7 forms of seven years and secondary school, edition 6, revised (1951); «Grammar of Ukrainian Language. Part I and II. Schoolbook for the 6-7 forms of seven years and secondary school» (1953); A.P.Medushevs’kyi, M.K.Tyshchenko «Syntax of Ukrainian Language» (1960) have been analyzed in the article. Their positive sides: accordance to the program, to orthography of that time, variety of exercises, part of the old examples to the rules changed into the ones, taken from the works of the best Ukrainian writers, have been mentioned. Their drawbacks were mentioned as well: overstrain with theoretical material, uniformity of tasks, insufficiently tasks for speech development. The role of the Ministry of Education of Ukrainian SSR in improvement schoolbooks has been revealed.